2004
DOI: 10.1021/ja031855p
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed C−H Homocoupling of Thiophenes:  Facile Construction of Bithiophene Structure

Abstract: Palladium-catalyzed C-H homocoupling of thiophene derivatives takes place in the presence of silver(I) fluoride or acetate. A variety of bithiophenes are obtained in good to excellent yields. In particular, the reaction of 2-bromothiophene proceeds at room temperature to afford 5,5'-dibromo-2,2'-bithiophene, where the bromine atom is completely intact in the palladium-catalyzed reaction. XRD analysis reveals that silver fluoride is reduced to silver(0) during the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
0
4

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(102 citation statements)
references
References 21 publications
1
95
0
4
Order By: Relevance
“…B. als organische Dünn-filmtransistoren, Flüssigkristalle oder Solarzellen in der Elektronik und Photonik von Bedeutung sind. [58] 2-Arylpyridine konnten in der chelatkontrollierten palladiumkatalysierten dehydrierenden Homokupplung mit Pd-(OAc) 2 als Katalysator und Oxon als stöchiometrischem Oxidationsmittel umgesetzt werden (Schema 30). [59] Interessanterweise verliefen diese Umsetzungen selbst bei Umgebungstemperatur mit hoher Effizienz.…”
Section: Eisenkatalysierte Direkte Arylierungen Mit Metallorganischenunclassified
“…B. als organische Dünn-filmtransistoren, Flüssigkristalle oder Solarzellen in der Elektronik und Photonik von Bedeutung sind. [58] 2-Arylpyridine konnten in der chelatkontrollierten palladiumkatalysierten dehydrierenden Homokupplung mit Pd-(OAc) 2 als Katalysator und Oxon als stöchiometrischem Oxidationsmittel umgesetzt werden (Schema 30). [59] Interessanterweise verliefen diese Umsetzungen selbst bei Umgebungstemperatur mit hoher Effizienz.…”
Section: Eisenkatalysierte Direkte Arylierungen Mit Metallorganischenunclassified
“…Hence, Ag + ions can be considered as terminal oxidants in these reactions. [15] The role of the Cu 2+ ions is less clear at present. We assume that, in analogy to the Wacker process, [16] Cu 2+ ions catalyze the oxidation of Pd 0 by O 2 when substoichiometric amounts of Ag + ions are applied (Table 1, entries 6 and 7).…”
Section: +mentioning
confidence: 98%
“…We found that homocoupling of thiophenes took place at the CH bond adjacent to the sulfur atom by treatment of a catalytic amount of palladium and silver(I) fluoride. 24 Several thiophene derivatives bearing a substituent such as formyl, ethoxycarbonyl, acetyl, methyl, and aryl groups underwent the reaction. Benzothiophene and a thiazole derivative (5-position) also homocoupled smoothly as summarized in Table 14.…”
Section: Reactions At the Ch Bond Of Thiophene Derivativesmentioning
confidence: 99%